2008
DOI: 10.1177/1742395308090069
|View full text |Cite
|
Sign up to set email alerts
|

'Normal, but...': living with type 2 diabetes in Bangkok, Thailand

Abstract: The diabetes qualification ('normal, but...') acted as a bridge between health and illness, enabling people to separate their physical health status, perceived as being particularly flawed by having diabetes, from their 'normal' social self. The sustained idea of the normality of the embodied and socially embedded self implied that the disease was under control, ensuring its minimal intrusion into social relationships and practical living.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
2
7
0
1
Order By: Relevance
“…Our findings support and extend those from previous studies (most based on narrative interviews of people with diabetes, and a single ethnographic study) which highlighted the need to align the self-management agenda with the social demands of people's everyday lives; their need to maintain a coherent identity and a "normal" social life; and the finding that poverty and the physical and social environment may impact on self-management [21,25,31,43]. In particular, our findings resonate strongly with those of a previous study by our team which highlighted a number of 'storylines' within which the practical tasks of self-management acquire social meaning and moral worth, including rebuilding spoiled identity, living a disciplined and balanced life, mobilising a care network, navigating and negotiating in the health care system, and making ethical choices (such as allocating a limited family budget) [25].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings support and extend those from previous studies (most based on narrative interviews of people with diabetes, and a single ethnographic study) which highlighted the need to align the self-management agenda with the social demands of people's everyday lives; their need to maintain a coherent identity and a "normal" social life; and the finding that poverty and the physical and social environment may impact on self-management [21,25,31,43]. In particular, our findings resonate strongly with those of a previous study by our team which highlighted a number of 'storylines' within which the practical tasks of self-management acquire social meaning and moral worth, including rebuilding spoiled identity, living a disciplined and balanced life, mobilising a care network, navigating and negotiating in the health care system, and making ethical choices (such as allocating a limited family budget) [25].…”
Section: Resultssupporting
confidence: 87%
“…More recently, Korean researchers observed eating practices in 15 people with diabetes and concluded that cultural meanings were important in food choices [30]. An ethnographic study in Thailand of 33 people with diabetes found no evidence of "spoiled identity", perhaps because diabetes did not have visible manifestations in most people; but participants spent much time and effort in self-management work (diet control, exercise, clinic attendance, self-monitoring) in order to achieve what they described as "normality" [31]. …”
Section: Introductionmentioning
confidence: 99%
“…In these studies, participants expressed belief that diabetes was a short term condition with the oral anti-diabetic agents providing symptomatic relief but were unneeded once they ‘felt well’, 21 , 29 , 30 , 31 only to restart on them when their illness was visible and possibly affecting their daily routines. 32 Such reports are similar to reports from studies conducted among Ethiopian patients with diabetes which also reported ‘feeling of being well without treatment’ and ‘disappearance of symptoms’ as reasons for low adherence to anti-diabetic medications. 12 , 33 This finding is also supported by other studies from the Ethiopian context where more emphasis is given to symptomatic, acute conditions and where hope for a cure is expressed.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, research has found a negative influence of the disease on family and social life ( de Silva et al, 2012 ; Manderson & Kokanovic, 2009 ). However, a Thai study has found that women define themselves as being “normal” when they can work and perform daily activities of their usual lives even if they have diabetes ( Naemiratch & Manderson, 2008 ). Another study of Thai Buddhist and Muslim women with T2D mentions religion as a significant factor that promotes psychosocial well-being when living with the disease ( Lundberg & Thrakul, 2013 ), and one of the Buddhist teachings indicates illness as a common element in the cycle of human life ( Phromtha, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…The oft-mentioned lack of empirical studies that consider the lives of Asian people with diabetes ( Li, Drury, & Taylor, 2013 ; Lundberg & Thrakul, 2013 ; Naemiratch & Manderson, 2008 ; Sowattanangoon et al, 2009 ; Yamakawa & Makimoto, 2008 ) and the high prevalence and morbidity of T2D as one of the top five chronic diseases in Thailand ( Bureau of Epidemiology, Ministry of Public Health, 2013 ) encourage the understanding of how people perceive their lives with this disease. Moreover, the higher diabetes prevalence among Thai women makes it important to focus a study on their perceptions ( Bureau of Epidemiology, Ministry of Public Health, 2013 ).…”
Section: Introductionmentioning
confidence: 99%